The medial olivocochlear reflex in children during active listening. (August 2015) - Smith, Spencer B.; Cone, Barbara
Abstract: Objective: To determine if active listening modulates the strength of the medial olivocochlear (MOC) reflex in children. Design: Click-evoked otoacoustic emissions (CEOAEs) were recorded from the right ear in quiet and in four test conditions: one with contralateral broadband noise (BBN) only, and three with active listening tasks wherein attention was directed to speech embedded in contralateral BBN. Study sample: Fifteen typically-developing children (ranging in age from 8 to14 years) with normal hearing. Results: CEOAE levels were reduced in every condition with contralateral acoustic stimulus (CAS) when compared to preceding quiet conditions. There was an additional systematic decrease in CEOAE level with increased listening task difficulty, although this effect was very small. These CEOAE level differences were most apparent in the 8–18 ms region after click onset. Conclusions: Active listening may change the strength of the MOC reflex in children, although the effects reported here are very subtle. Further studies are needed to verify that task difficulty modulates the activity of the MOC reflex in children.